INTERNALISASI NILAI-NILAI SPIRITUAL PADA DIRI SISWA DI SMPN 2 KOTA BENGKULU - Ediyono Ediyono (UIN Fatmawati Sukarno Bengkulu, 2018)
This research describes the condition of students’ spiritual attitudes, methods used by Master and the constraints and support of the internalization process of spiritual value itself. This research used qualitative descriptive and interactive method with observation, documentation, observation and interview. The result of the research is that before the internalization of these spiritual values, the condition of understanding and religious practice is still far from being expected. Meanwhile, after the in- ternalization is performed, the result of difference is increase the awareness of students to implement and practice the worship, especially mandatory prayer in congregation. Morals and behaviors are increase and the respect for teachers also increase so that this affects the increase in student achievement itself. Methods used include Teacher Role Improvement Method, Guid- ance and Counseling Method, Tauladan Method, Cultural Method, and Tabligh Method. While the inhibiting factors are the background of family conditions and the limited role of teachers in conducting guidance and learning. The supporting factor is the application of K-13 curriculum which is very compatible with the activities of spiritual values in the students. The teachers awareness in giving tauladan to their students also increase